Crescimento da Gliricidia sepium submetida a diferentes manejos de corte nas condições do semiárido cearense - Edvan, Ricardo Loiola (2013)
The objective was to evaluate the growth of Glirídica sepium under different managements cutting conditions semiarid of Ceará. The statistical design was a randomized block design with split plots. The plots consisted of four cut off frequencies (45, 60, 75 and 90 days) and three heights residue (30, 60 and 90 cm) with four replications, and the cut off frequency comprised the major portion of the residue height of the subplot. The experiment was conducted in the city of Fortaleza, Ceará. Planting took place in March 2010 at a spacing of 1.5 m x 1.0 m with an area of 600 m2 and experimental stand with 336 plants. Cutting standardization and application of treatments occurred in December 2010, from this date began the evaluation period of 375 days which was the amount of cuts varied with treatments, performing 8, 6, 5 and 4 cuts for treatments with cut off frequencies of 45, 60, 75 and 90 days, respectively. The analysis of the growth characteristics of Gliricidia was obtained by specific leaf area, leaf area index, relative growth rate, net assimilation rate, crop growth rate, stem diameter at ground level, diameter of shoots, number of sprouting, number of leaves, plant height, leaf/stem ratio, plant dry matter, leaf and stem dry mass of leaf and stem by cutting and total production of dry matter per cutting and full. Plants managed with cut off frequency of 90 days and a residue height of 90 cm had higher specific leaf area and leaf area index with 48.51 cm2.g-1 and 5.54, respectively. The highest growth rate cultural was 2.63 g.m-2.dia-1 obtained in the management of cutting frequency of 45 days and residue height of 90 cm. At the same management cut off was observed for the maximum relative growth rate which was 0.016 g.g-1.dia-1 and higher net assimilation rate with 1.32 g.m-2.dia-1, both rates were obtained in period of 3° to 4° cut (rainy season). The diameter of the bud for handling cut frequently with 90 days combined residue height of 90 cm was 0.31 cm larger than the diameter of the shoot in the management of cutting frequency of 45 days and residue height of 30 cm, with larger diameter of 0.96 cm shoot for the rainy season and 0.81 cm for the dry period, getting even, greater leaf area index during the rainy season and dry. The handling with cut off frequency of 90 days combined with residue height of 90 cm obtained higher dry matter accumulation by cutting forage during the rainy season and dry with 5.3 and 4.8 t.ha-1, and with full 10.7 t.ha-1 and 9.7, respectively. Plants subjected to the same management reached the highest yield of green mass and dry fodder by cutting, with a mean of 18.13 t.ha-1 and 5.09 t.ha-1 in each cut, respectively, producing 72 52 t.ha-1 fresh weight of total forage and 20.36 t.ha-1 dry weight of total forage. The cut off frequency and height of residue influence the growth and production of Gliricidia. The intensity of cut 90 cm provides better growth rates and when combined with a cut off frequency of 90 days is greater herbage mass production of Gliricidia.